The Internet-Based Business Model and Corporate Risk-Taking: An Empirical Study from the Information Empowerment Perspective. (15th June 2022) - Li, Lei; Yang, Shuili
Abstract : Reasonable risk-taking acts as a solid foreground for sustaining corporate growth. Having companies trading on Chinese stock exchanges between 2010 and 2019 sampled, this paper explored how an Internet-based business model would affect corporate risk-taking from the perspective of information empowerment. Through the mediation effect model and quantitative text analysis, the following findings were obtained here. First, a network-powered business model could significantly enhance the risk tolerance of companies. Second, mechanism testing showed that such a novel model would help reduce the asymmetry of corporate information and thus enhance corporate risk-taking capacity. Third, an analysis on heterogeneity revealed that businesses that enjoy a freer market and fewer financing constraints could better feel the positive impact of an Internet-based business model on corporate risk-taking. Fourth, an examination of economic consequences showed that risk-taking under Internet-based business models allowed enterprises to create sustainable value. Overall, the present work confirmed the positive impact of an Internet-based business model on corporate risk-taking from the information empowerment angle, and it is expected to provide a theoretical basis for enterprises to optimize their investment decision-making strategies and increase their risk-taking willingness and capacity.